Voice of Protest in Nepali Poetry by Women - Mishra, Indira Acharya (Molung Educational Frontier, 2020)
This article explores feminist voice in selected poems of four Nepali female poets. They are: "Ma Eutā Chyātieko Poshtar" ["I, a Frayed Poster"] by Banira Giri, "Pothī Bāsnu Hudaina" ["A Hen Must not Crow"] by Kunta Sharma,"Ma Strī Arthāt Āimai"["I am a Female or a Woman"] by Seema Aavas and "Tuhāu Tyo Garvalai" ["Abort the Female Foetus"] by Pranika Koyu. In the selected poems they protest patriarchy and subvert patriarchal norms and values that trivialize women. The tone of their poems is sarcastic towards male chauvinism that treats women as a second-class citizen. The poets question and ridicule the restrictive feminine gender roles that limit women's opportunity. To examine the voice of protest against patriarchy in the selected poems, the article takes theoretical support from French feminism, though not limited to it. The finding of the article suggests that Nepali women have used the genre to the political end, as a medium to advocate women's rights.